A method for preparing and use of a self-assembling skin care product of recombinant collagen type iii
Patent Information
- Application Number
- CN202610829212.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-06-10
AI Technical Summary
[0007]本发明针对现有胶原蛋白技术中存在活性成分难以兼顾稳定性、协同增效性、透皮效率与皮肤耐受性的问题,提供了一种重组Ⅲ型胶原蛋白的自组装护肤品的制备方法和应用
1.卓越的稳定性:超分子网络对活性成分(尤其是异鼠李素和苦参碱)形成多重保护,有效隔绝光、氧、热等因素。加速试验(40℃,75%RH,3个月)表明,异鼠李素和苦参碱的保留率均超过90%,远高于其在简单乳液中的保留率(通常低于60%)。
Smart Images

Figure CN122351074B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of cosmetic technology, and in particular relates to a method for preparing and applying a self-assembled skin care product based on recombinant type III collagen. Background Technology
[0002] In the functional cosmetics market, collagen is widely used in anti-aging and repair products due to its excellent biocompatibility and repair activity. Recombinant type III collagen overcomes the immunogenicity risks of animal-derived collagen and has become a current research hotspot. However, existing recombinant type III collagen still has the following inherent defects and technical limitations in practical applications: 1. Poor stability: Recombinant type III collagen is easily affected by temperature, light, pH, and enzymatic hydrolysis in aqueous formulations, resulting in denaturation, degradation, or aggregation, leading to the destruction of the triple helix structure and rapid loss of biological activity. Existing stabilization methods such as low-temperature storage and the addition of preservatives have limited effectiveness and cannot maintain its natural conformation in room-temperature liquid formulations for extended periods.
[0003] 2. Low transdermal penetration and skin retention efficiency: Recombinant type III collagen has a relatively large molecular weight, making it difficult to effectively penetrate the stratum corneum barrier. Most of it remains on the skin surface and is quickly lost after washing or wiping, resulting in extremely low bioavailability. Even when using small molecule collagen peptides, their irregular coiled structure lacks targeted binding ability, and both penetration depth and retention time are unsatisfactory.
[0004] 3. Insufficient synergy among multiple components: Existing formulas often involve simple physical mixing of collagen with other active ingredients such as flavonoids and alkaloids. Each component is released independently, failing to form an ordered assembly structure at the molecular level. This results in a limitation where the actual repair and anti-wrinkle effects are not fully synergistic, making it difficult to meet the multi-dimensional anti-aging needs.
[0005] 4. A prominent contradiction exists between high efficacy and high tolerability: Increasing collagen concentration to enhance anti-aging effects can easily lead to sticky skin, an excessive film-like feeling, or even irritation; conversely, lowering the concentration results in diminished efficacy. Existing recombinant technologies have not resolved the balance between formula compatibility and low irritation at high concentrations.
[0006] 5. High industrial production costs: The stabilization process of active collagen is complex, and the investment in technologies and equipment such as freeze drying and liposome encapsulation is large, with significant batch-to-batch differences, resulting in high prices for the final product. Summary of the Invention
[0007] This invention addresses the problem in existing collagen technology that it is difficult to simultaneously ensure the stability, synergistic effect, transdermal efficiency, and skin tolerance of active ingredients, and provides a method for preparing and applying a self-assembled skin care product based on recombinant type III collagen.
[0008] One of the objectives of this invention is to provide a functional composition based on molecular self-assembly, wherein the functional composition comprises, by mass percentage: 0.1%-8.0% lichen polysaccharide, 0.05%-5.0% recombinant type III collagen, 0.005%-1.0% isorhamnetin, and 0.01%-2.0% matrine.
[0009] In a preferred embodiment of the present invention, the functional composition comprises, by weight percentage, the following components: 0.5%-5.0% lichen polysaccharide, 0.1%-3.0% recombinant type III collagen, 0.01%-0.5% isorhamnetin, and 0.05%-1.0% matrine.
[0010] In a preferred embodiment of the present invention, the preparation steps of the functional composition are as follows: S1: Add lichen polysaccharide to deionized water while stirring, and continue stirring at 40-60℃ until completely dissolved to form a homogeneous and transparent colloidal solution. Cool to room temperature to obtain phase A. S2: Add recombinant type III collagen to deionized water and stir or swell until completely dissolved at room temperature to obtain phase B; S3: Under low-speed stirring conditions, phase B obtained in S2 is added dropwise to phase A obtained in S1. After the addition is complete, stirring is continued for 30-90 minutes to form a primary gel network through self-assembly. S4: Dissolve isorhamnetin and matrine together in a polyol, and heat to aid dissolution to obtain phase C; S5: Under low-speed stirring conditions, phase C obtained in S4 is added dropwise to the primary gel network obtained in S3. After the addition is complete, the resulting mixture is transferred to a homogenizer for homogenization, allowed to stand and mature, and the pH value is adjusted to 5.5-6.5. The functional composition is obtained by vacuum degassing and filtration.
[0011] In a preferred embodiment of the present invention, the room temperature mentioned in S1 and S2 is 20-25°C.
[0012] In a preferred embodiment of the present invention, the low-speed stirring conditions described in S3 and S5 are 200-400 rpm.
[0013] In a preferred embodiment of the present invention, the polyol in S4 includes, but is not limited to, propylene glycol, butanediol or glycerol; the heating to aid dissolution condition is: temperature ≤ 50°C.
[0014] In a preferred embodiment of the present invention, the homogenization conditions in S5 are: a rotation speed of 8000-15000 rpm and a time of 3-10 minutes.
[0015] In a preferred embodiment of the present invention, the conditions for static curing in S5 are: temperature of 35-45°C and time of 1-3 hours.
[0016] A second objective of this invention is to provide a self-assembled skincare product of recombinant type III collagen, wherein the cosmetic contains the above-mentioned functional composition, as well as a cosmetically acceptable carrier and excipients.
[0017] A third objective of this invention is to provide the application of the above-mentioned functional composition in the preparation of anti-aging and skin barrier repair cosmetics.
[0018] Compared with existing technologies, the beneficial effects of this invention are as follows: Addressing the shortcomings and limitations of existing collagen in terms of stability, permeability, synergy, tolerability, and cost control, this invention designs an improved method based on a supramolecular self-assembly system. This supramolecular system forms an ordered assembly structure through intermolecular non-covalent interactions, exhibiting significant advantages in stabilizing and maintaining collagen activity, promoting transdermal penetration and retention, achieving synergistic effects of multiple components, balancing efficacy and tolerability, and simplifying the production process.
[0019] This invention provides a self-assembled skincare product of recombinant type III collagen, the self-assembled skincare product containing a functional composition, the functional composition comprising, by mass percentage: 0.1%-8.0% lichen polysaccharide, 0.05%-5.0% recombinant type III collagen, 0.005%-1.0% isorhamnetin, and 0.01%-2.0% matrine.
[0020] Among them, lichen polysaccharide is a carboxymethylated, β1,3-linked linear D-glucan with a molecular weight ranging from 5 kDa to 100 kDa; its structure contains carboxymethyl (COO) - It provides a negative charge, which can generate a strong electrostatic attraction with the positively charged groups of collagen; its molecular chain can form a helical conformation through intramolecular hydrogen bonds, forming a hydrophobic cavity inside, which is used to encapsulate hydrophobic active ingredients.
[0021] Recombinant type III collagen has a molecular weight range of 30 kDa to 150 kDa. Its peptide chain contains abundant glycine-proline-hydroxyproline (Gly-XY) repeating sequences, forming a stable triple helix structure. The lysine and arginine residues on its side chains are protonated under the specified pH conditions to form NH3. + It is a key site for electrostatic interaction; the aromatic amino acids it contains (such as phenylalanine and tyrosine) provide the structural basis for π-π stacking.
[0022] Isorhamnetin belongs to the flavonoid aglycone family. Its molecule contains a planar aromatic ring structure of benzopyranone and multiple phenolic hydroxyl groups. Its hydrophobic aromatic ring can be encapsulated by the hydrophobic cavity of lichen polysaccharide. Its phenolic hydroxyl groups can form hydrogen bonds with collagen. Its aromatic ring can undergo π-π stacking with the aromatic side chains of collagen.
[0023] Matrine belongs to the quinolone alkaloid class. Its molecule contains a rigid quinolone ring structure and has a certain degree of hydrophobicity. It can be effectively encapsulated by the hydrophobic cavity of lichen polysaccharide, and the CH bond at the edge of its molecule can form a weak electrostatic interaction with the polysaccharide chain.
[0024] This invention utilizes the specific molecular structures among the above four components to spontaneously self-assemble into an integrated network under mild conditions through the following four types of non-covalent interactions: (1) Electrostatic attraction: COO of lichen polysaccharide - With recombinant type III collagen NH3 + Ionic bonds are formed between them, forming the rigid framework of the entire supramolecular network. (2) Hydrophobic interaction and host-guest inclusion: The hydrophobic cavity formed by the helical structure of lichen polysaccharide, as the "host", includes the hydrophobic aromatic ring parts of isorhamnetin and matrine as "guests" through hydrophobic interactions, thereby achieving solubilization, protection and sustained release. (3) Hydrogen bond: It is widely present between the components, such as the hydroxyl group of lichen polysaccharide and the peptide bond / carboxyl group of collagen, and the phenolic hydroxyl group of isorhamnetin and the hydrogen donor / acceptor atom of collagen, which play a role in strengthening and stabilizing the network. (4) π-π stacking: The benzopyranone plane of isorhamnetin and the benzene ring plane of aromatic amino acids (such as phenylalanine) in recombinant type III collagen overlap in an approximately parallel manner (dihedral angle <20°), forming face-to-face stacking, which further enhances the positioning and stability of isorhamnetin in the network. Thus, it can be seen that the present invention, through the synergistic and mutually reinforcing effects of the above four types of actions, ultimately forms a dynamic and stable three-dimensional supramolecular network with "lichen polysaccharide-collagen electrostatic framework" as the core, and isorhamnetin and matrine encapsulated and fixed through secondary actions.
[0025] The self-assembled skincare product containing a functional composition provided by this invention has the following significant advantages compared with the prior art: 1. Excellent stability: The supramolecular network provides multiple layers of protection for the active ingredients (especially isorhamnetin and matrine), effectively isolating them from factors such as light, oxygen, and heat. Accelerated tests (40℃, 75%RH, 3 months) show that the retention rates of isorhamnetin and matrine both exceed 90%, which is much higher than their retention rates in simple emulsions (usually below 60%).
[0026] 2. Significant synergistic effects: The four components form a functionally integrated network through non-covalent bonds. The repair (collagen), antioxidant (isorhamnoside), anti-inflammatory and antibacterial (matrine), and moisturizing and film-forming (lichen polysaccharide) effects are not simply additive, but mutually reinforcing. In vitro cell experiments show that the repair efficiency of this composition on human keratinocytes damaged by oxidative stress is 2.1 times higher than that of a physical mixture of four components.
[0027] 3. Excellent penetration and long-lasting sustained release: The hydrophilic film formed by lichen polysaccharides on the skin combines with the adhesion-promoting properties of collagen to promote the transdermal penetration of active ingredients. Franz diffusion cell experiments showed that the cumulative penetration of isorhamnetin over 24 hours was 1.8 times that of ordinary liposomes. Simultaneously, the supramolecular network provides sustained release, allowing the active ingredient to be released for more than 8 hours.
[0028] 4. Good safety and tolerability: Through inclusion and network fixation, the potential irritation caused by direct skin contact of isorhamnetin and matrine is reduced. Human patch tests show that this composition has an irritation level of 0 (non-irritating) and is suitable for sensitive skin.
[0029] 5. The preparation process is green and simple: the entire self-assembly process is carried out in a mild aqueous phase, without the need for organic solvents or complex chemical reactions, with low energy consumption, making it suitable for industrial-scale production. Attached Figure Description
[0030] Figure 1 The graph shows the results of the long-term storage stability test of free recombinant type III collagen and functional composition at 25°C. Figure 2 The graph shows the results of accelerated stability testing of free recombinant type III collagen and functional compositions at 40°C. Figure 3 The circular dichroism chromatogram of free recombinant type III collagen and functional composition after heat treatment at 50°C is shown. Figure 4 A statistical chart showing the degradation rate of free recombinant type III collagen and functional compositions under different pH conditions over 24 hours; Figure 5 Scanning electron microscopy image of free recombinant type III collagen; Figure 6 Scanning electron microscope images of the functional composition; Figure 7 A statistical chart showing the activity retention rate of free recombinant type III collagen and functional compositions after storage at 4°C for 3 months; Figure 8 A statistical chart showing the activity retention rate of free recombinant type III collagen and functional compositions after storage at 25°C for 6 months; Figure 9The cumulative permeation time of free recombinant type III collagen and functional composition in vitro through transdermal absorption. Figure 10 This is a statistical chart showing the amount of collagen retained in the stratum corneum, epidermis, and dermis after a 24-hour transdermal test of free recombinant type III collagen and functional compositions. Figure 11 Laser confocal microscopy image of free recombinant type III collagen; Figure 12 Laser confocal microscopy images of functional composite materials; Figure 13 A statistical chart showing the 24-hour transdermal absorption rate of free recombinant type III collagen and functional compositions; Figure 14 Statistical graph of DPPH free radical scavenging rate for different treatment groups; Figure 15 Fourier transform infrared spectra of different treatment groups are overlaid. Figure 16 X-ray diffraction pattern of the functional composition; Figure 17 This is a dynamic light scattering particle size distribution diagram of the functional composition; Figure 18 Zeta potential bar chart comparing blank carrier, free recombinant type III collagen, and functional composition; Figure 19 A statistical chart showing the retention rates of free isorhamnetin, traditional liposome encapsulation, and functional compositions under light conditions; Figure 20 A statistical chart showing the retention rates of free isorhamnetin, traditional liposome encapsulation, and functional compositions after high-temperature treatment at 50°C for 24 hours; Figure 21 A statistical chart showing the retention rates of free isorhamnetin and functional compositions during long-term storage at 25°C. Figure 22 Line graph showing the changes in TEWL values for different treatment groups at 0, 1, 3, 5, and 7 days; Figure 23 A bar chart comparing the TEWL values of different treatment groups on day 7; Figure 24 A bar chart comparing skin hydration levels in different treatment groups on day 7. Figure 25 The in vitro cumulative release rate-time curves of free isorhamnetin, isorhamnetin encapsulated in conventional liposomes, and functional compositions are shown. Figure 26 A bar chart comparing the minimum inhibitory concentrations (MICs) of blank carrier, free matrine, matrine encapsulated in traditional liposomes, and functional compositions against Propionibacterium acnes. Figure 27 A statistical graph showing the effect of different concentrations of blank carrier and functional composition on the survival rate of HaCaT cells; Figure 28 Statistical graph of chicken embryo allantoic membrane stimulation scores for blank carrier and functional composition; Figure 29 A statistical graph showing the hemolysis rate of erythrocytes in the blank carrier and the functional composition; Figure 30 Statistical graph of collagen content in skin tissue of different treatment groups; Figure 31 A statistical chart showing the hydroxyproline content in skin tissues of different treatment groups. Detailed Implementation
[0031] Those skilled in the art can refer to the content of this document and appropriately improve the process parameters to achieve the desired results. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments, and those skilled in the art can obviously make modifications or appropriate alterations and combinations to the methods and applications described herein without departing from the content and scope of this invention to implement and apply the technology of this invention.
[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.
[0033] Example 1: A functional composition based on molecular self-assembly The functional composition prepared in this embodiment consists of: 1.0% lichen polysaccharide, 0.8% recombinant type III collagen, 0.1% isorhamnetin, 0.2% matrine, and the balance being deionized water.
[0034] S1: Weigh 80g of deionized water into a beaker, heat to 50℃, add 1.0g of lichen polysaccharide (carboxymethylated, Mw≈50kDa) while stirring at 400rpm, keep warm and stir for 1 hour until completely dissolved, cool to 25℃ to obtain phase A; S2: Weigh 10g of deionized water into a beaker, add 0.8g of recombinant type III collagen (Mw≈100kDa) at 25℃, stir or swell until completely dissolved to obtain phase B; S3: Under low-speed stirring at 300 rpm, phase B obtained in S2 is added dropwise to phase A obtained in S1. After the addition is complete, stirring is continued for 60 minutes to form a primary gel network through self-assembly. S4: Dissolve 0.1g of isorhamnetin and 0.2g of matrine together in 3.0g of deionized water, and sonicate in a water bath at 45℃ for 5 minutes to obtain phase C; S5: Under low-speed stirring at 300 rpm, phase C obtained in S4 was added dropwise to the primary gel network obtained in S3. After the addition was complete, the resulting mixture was transferred to a homogenizer for homogenization (12000 rpm for 8 minutes). Then, the beaker was placed on a magnetic stirrer and allowed to stand and mature at 37°C in the dark for 2 hours. The pH of the system was adjusted to 6.0 using a 1% citric acid solution. Deionized water was added to bring the total weight to 100 g. The mixture was then degassed under vacuum and filtered through a 200-mesh filter cloth to obtain the functional composition.
[0035] Example 2: Preparation of supramolecular repair essence The supramolecular repair essence prepared in this embodiment consists of: a functional composition (specifically: 1.0% lichen polysaccharide, 0.8% recombinant type III collagen, 0.1% isorhamnetin, 0.2% matrine), 5.0% glycerol, 3.0% 1,3-propanediol, 0.2% xanthan gum, 0.5% p-hydroxyacetophenone, and the balance being deionized water.
[0036] S1: Weigh 80g of deionized water into a beaker, heat to 50℃, add 1.0g of lichen polysaccharide (carboxymethylated, Mw≈50kDa) while stirring at 400rpm, keep warm and stir for 1 hour until completely dissolved, cool to 25℃ to obtain phase A; S2: Weigh 10g of deionized water into a beaker, add 0.8g of recombinant type III collagen (Mw≈100kDa) at 25℃, stir or swell until completely dissolved to obtain phase B; S3: Under low-speed stirring at 300 rpm, phase B obtained in S2 is added dropwise to phase A obtained in S1. After the addition is complete, stirring is continued for 60 minutes to form a primary gel network through self-assembly. S4: Dissolve 0.1g isorhamnetin and 0.2g matrine together in 3.0g 1,3-propanediol, and sonicate in a water bath at 45℃ for 5 minutes to obtain phase C; S5: Under low-speed stirring at 300 rpm, phase C obtained in S4 was added dropwise to the primary gel network obtained in S3. After the addition was complete, the resulting mixture was homogenized in a homogenizer (12000 rpm for 8 minutes). Then, the beaker was placed on a magnetic stirrer and allowed to stand and mature at 37°C in the dark for 2 hours. 5.0 g of glycerol and 0.2 g of xanthan gum slurry pre-dispersed with deionized water were added to the matured system and stirred evenly. The pH of the system was adjusted to 6.0 using 1% citric acid solution. 0.5 g of p-hydroxyacetophenone was added, and deionized water was added to bring the total weight to 100 g. The mixture was then degassed under vacuum and filtered through a 200-mesh filter to obtain the supramolecular repair essence.
[0037] Example 3: Preparation of supramolecular repair mask liquid The supramolecular repair mask liquid prepared in this embodiment consists of: a functional composition (specifically: 2.5% lichen polysaccharide, 1.5% recombinant type III collagen, 0.05% isorhamnetin, 0.4% matrine), 8.0% butylene glycol, 0.5% panthenol, 0.15% xanthan gum, 0.3% ethylhexylglycerin, and the balance being deionized water.
[0038] S1: Weigh 80g of deionized water into a beaker, heat to 50℃, add 2.5g of lichen polysaccharide (carboxymethylated, Mw≈80kDa) and 0.15g of xanthan gum while stirring at 400rpm, keep warm and stir for 1 hour until completely dissolved, cool to 25℃ to obtain phase A; S2: Weigh 10g of deionized water into a beaker, add 1.5g of recombinant type III collagen (Mw≈70kDa) at 25℃, stir or swell until completely dissolved to obtain phase B; S3: Under low-speed stirring at 300 rpm, phase B obtained in S2 is added dropwise to phase A obtained in S1. After the addition is complete, stirring is continued for 60 minutes to form a primary gel network through self-assembly. S4: Dissolve 0.05g isorhamnetin and 0.4g matrine together in 8.0g butanediol, and sonicate in a water bath at 45℃ for 5 minutes to obtain phase C; S5: Under low-speed stirring at 300 rpm, phase C obtained in S4 was added dropwise to the primary gel network obtained in S3. After the addition was complete, the resulting mixture was transferred to a homogenizer for homogenization (12000 rpm for 8 minutes). Then, the beaker was placed on a magnetic stirrer and allowed to stand and mature at 37°C in the dark for 2 hours. 0.5 g panthenol and 0.3 g ethylhexylglycerin were added to the matured system and stirred until homogeneous. The pH of the system was adjusted to 6.0 using a 1% citric acid solution. Deionized water was added to bring the total weight to 100 g. The mixture was then degassed under vacuum and filtered through a 200-mesh filter to obtain the supramolecular repair mask liquid.
[0039] Example 4: Preparation of a supramolecular repair face cream The supramolecular repair cream prepared in this embodiment consists of an oil phase and an aqueous phase (O / W type). The oil phase composition is: 5.0% caprylic / capric triglyceride, 3.0% squalane, 1.5% cetearyl alcohol, 1.0% polydimethylsiloxane, and 0.5% tocopheryl acetate; The aqueous phase composition is as follows: functional composition (specifically: 0.8% lichen polysaccharide, 0.3% recombinant type III collagen, 0.3% isorhamnetin, 0.08% matrine, and 4.0% glycerol, 2.0% 1,2-pentanediol, 2.0% PEG100 stearate / glyceryl stearate, 0.1% carbomer (calculated as Carbopol 980), with the balance being deionized water.
[0040] S1: Weigh 80g of deionized water into a beaker, heat to 50℃, and add 0.8g of lichen polysaccharide (carboxymethylated, Mw≈30kDa) and 0.1g of carbomer (pre-dispersed in some glycerol) while stirring at 400rpm. Keep warm and stir for 1 hour until completely dissolved, and cool to 25℃ to obtain phase A; S2: Weigh 10g of deionized water into a beaker, add 0.3g of recombinant type III collagen (Mw≈120kDa) at 25℃, stir or swell until completely dissolved to obtain phase B; S3: Under low-speed stirring at 300 rpm, phase B obtained in S2 is added dropwise to phase A obtained in S1. After the addition is complete, stirring is continued for 60 minutes to form a primary gel network through self-assembly. S4: Dissolve 0.3g of isorhamnetin and 0.08g of matrine together in 2.0g of 1,3-propanediol, and sonicate in a water bath at 45℃ for 5 minutes to obtain phase C; S5: Under low-speed stirring at 300 rpm, phase C obtained in S4 was added dropwise to the primary gel network obtained in S3. After the addition was complete, the resulting mixture was transferred to a homogenizer for homogenization (12000 rpm for 8 minutes). Then, the beaker was placed on a magnetic stirrer and allowed to stand and mature at 37°C in the dark for 2 hours. The remaining 2.0 g of glycerol and 2.0% PEG-100 stearate / glycerol stearate were added to the matured system and stirred until homogeneous to obtain the aqueous phase. S6: Mix 5.0g caprylic / capric triglyceride, 3.0g squalane, 1.5g cetearyl alcohol, 1.0g polydimethylsiloxane, and 0.5g tocopheryl acetate, and heat to 75°C to dissolve evenly to obtain the oil phase; S7: Heat the aqueous phase obtained in S5 to 75°C, add the oil phase obtained in S6 to the heated aqueous phase under high-speed stirring at 12000 rpm, homogenize and emulsify for 5 minutes, cool down to 40°C, neutralize the carbomer with triethanolamine and adjust the pH of the system to 6.0, continue stirring and cooling down to below 30°C to obtain the supramolecular repair cream.
[0041] Comparative Example 1: The physical mixture prepared in this comparative example consisted of: 1.0% lichen polysaccharide, 0.8% recombinant type III collagen, 0.1% isorhamnetin, 0.2% matrine, and the balance being deionized water; the preparation steps were as follows: S1: Weigh 80 g of deionized water into a beaker, and add 1.0 g of lichen polysaccharide (carboxymethylated, Mw≈50 kDa), 0.8 g of recombinant type III collagen (Mw≈100 kDa), 0.1 g of isorhamnetin, and 0.2 g of matrine at room temperature (25℃) to obtain a mixture; S2: Stir the mixture obtained in S1 at 400 rpm for 1 hour until all solid powders are evenly dispersed and there are no obvious particles. Adjust the pH of the system to 6.0 with 1% citric acid solution, add deionized water to a total weight of 100 g, and continue stirring for 30 minutes. After vacuum degassing and filtration through a 200-mesh filter cloth, a physical mixture is obtained.
[0042] Comparative Example 2: The composition of the conventional liposome-encapsulated isorhamnetin prepared in this comparative example is: 0.1% isorhamnetin, liposome carrier material (soy lecithin to cholesterol mass ratio of 4:1, total lipid concentration of 2%), and the balance being deionized water or phosphate buffer (pH 6.0); the preparation steps are as follows: S1: Weigh 0.8 g of soybean lecithin and 0.2 g of cholesterol, dissolve them together in 20 mL of anhydrous ethanol, and sonicate to dissolve them to form a clear lipid solution; S2: Add 0.1 g of isorhamnetin to the lipid solution obtained in S1, and continue to sonicate for 5 minutes to obtain the oil phase; S3: Under 40℃ water bath conditions, the oil phase obtained in S2 was slowly added dropwise to 60 mL of deionized water (preheated to 40℃) at a rate of 1 mL / min, while stirring at 500 rpm. After the addition was complete, stirring was continued for 30 minutes. Then, the mixture was transferred to a rotary evaporator and ethanol was removed under vacuum at 40℃ until the system was free of alcohol odor, thus obtaining a liposome suspension. S4: The liposome suspension obtained in S3 was subjected to probe sonication in an ice-water bath (power 200 W, sonication for 5 seconds / interval for 5 seconds, total time 10 minutes) to homogenize the particle size; it was then filtered and sterilized using a 0.22 μm filter membrane, and deionized water was added to a total weight of 100 g to obtain isorhamnetin encapsulated in conventional liposomes.
[0043] Comparative Example 3: The composition of the conventional liposome-encapsulated matrine prepared in this comparative example is: 0.2% matrine, liposome carrier material (soybean lecithin to cholesterol mass ratio of 4:1, total lipid concentration of 2%), and the balance being deionized water or phosphate buffer (pH 6.0); the preparation steps (ethanol injection method) are as follows: S1: Weigh 0.8 g of soybean lecithin and 0.2 g of cholesterol, dissolve them together in 20 mL of anhydrous ethanol, and sonicate to dissolve them to form a clear lipid solution; S2: Add 0.2 g matrine to the lipid solution obtained in S1, and sonicate for 5 minutes to obtain the oil phase; S3: Under 45℃ water bath conditions, the oil phase obtained in S2 was injected uniformly into 60 mL of deionized water (preheated to 45℃ and stirred at 500 rpm) using a syringe at an injection rate of 2 mL / min; after injection, stirring was continued for 30 minutes, and then the ethanol was removed by rotary evaporation under vacuum conditions at 45℃ to obtain a liposome suspension. S4: The liposome suspension obtained in S3 was subjected to probe sonication in an ice-water bath (power 150 W, sonication for 5 seconds / interval for 5 seconds, total time 8 minutes) to homogenize the particle size; sterilization was achieved by filtration using a 0.22 μm filter membrane, and deionized water was added to a total weight of 100 g to obtain traditional liposome-encapsulated matrine.
[0044] Effect Experiment: 1. Research on collagen stability and degradation To investigate the effect of the molecularly self-assembled functional composition provided by the present invention on the stability of recombinant type III collagen, the retention rate and structural changes of free recombinant type III collagen and the functional composition prepared in Example 1 were measured under different storage conditions.
[0045] (1) Long-term storage stability at 25℃ Free recombinant type III collagen and the functional composition prepared in Example 1 were stored at 25°C for 0, 7, 14, 30, 60, and 90 days, respectively, and the collagen retention rate was determined. Figure 1As shown, the free recombinant type III collagen experimental group reduced its collagen retention rate to approximately 9% after 90 days; while the functional composition experimental group maintained a collagen retention rate of over 78% after 90 days. This indicates that the supramolecular assembly system (functional composition) provided by this invention significantly improves the long-term stability of collagen at room temperature.
[0046] (2) Accelerated stability at 40℃ Free recombinant type III collagen and the functional composition prepared in Example 1 were stored at 40°C under accelerated conditions for 0, 1, 2, 3, and 4 weeks, respectively, and the collagen retention rate was measured. Figure 2 As shown, the free recombinant type III collagen experimental group reduced its collagen retention rate to approximately 7% after 4 weeks; while the functional composition experimental group maintained a collagen retention rate of over 79% after 4 weeks. This indicates that the supramolecular assembly system (functional composition) provided by this invention has good thermal stability.
[0047] (3) Circular dichroism (CD) analysis Free recombinant type III collagen and the functional composition prepared in Example 1 were respectively heat-treated at 50°C and then subjected to circular dichroism spectroscopy to evaluate the retention of the triple helix structure of collagen. Figure 3 As shown, compared to the functional composition experimental group, the characteristic peaks (positive peak at approximately 222 nm, negative peak at approximately 198 nm) of the free recombinant type III collagen experimental group were significantly weakened or even disappeared. This indicates that the supramolecular assembly system (functional composition) provided by this invention can maintain the typical collagen CD pattern, proving that supramolecular assembly effectively protects the secondary structure of collagen.
[0048] (4) pH stability Free recombinant type III collagen and the functional composition prepared in Example 1 were incubated at different pH values (5.0, 6.0, 7.0, 8.0) for 24 hours, and the degradation rate was measured. Figure 4 As shown, the degradation rate (38%-85%) of the free recombinant type III collagen experimental group under different pH conditions (5.0, 6.0, 7.0, 8.0) was higher than that of the functional composition experimental group (≤18%), especially under acidic conditions. This indicates that the supramolecular assembly system (functional composition) provided by the present invention has good pH stability and can effectively inhibit collagen degradation.
[0049] (5) Observation of morphology by scanning electron microscopy The free recombinant type III collagen and the functional composition prepared in Example 1 were observed using scanning electron microscopy. Figure 5-6As shown, the free recombinant type III collagen experimental group exhibited loose, amorphous aggregates, while the functional composition experimental group provided by this invention formed uniform, dense spherical or near-spherical nanostructures. This indicates that the supramolecular assembly system (functional composition) provided by this invention successfully encapsulates collagen and forms ordered assemblies.
[0050] (6) Long-term activity retention rate at low temperature and room temperature The activity retention rates of free recombinant type III collagen and the functional composition prepared in Example 1 were determined after storage at 4°C for 3 months and at 25°C for 6 months, respectively. Figure 7-8 As shown, at 4°C, the activity retention rate of the free recombinant type III collagen experimental group was only 38%, while the activity retention rate of the functional composition experimental group was as high as 94%; at 25°C, the activity retention rate of the free recombinant type III collagen experimental group was only 9%, while the activity retention rate of the functional composition experimental group was as high as 78%. This indicates that the supramolecular assembly system (functional composition) provided by the present invention can significantly improve the activity retention rate of collagen under various conditions.
[0051] 2. Transdermal absorption performance study The transdermal behavior of free recombinant type III collagen and the functional composition prepared in Example 1 was evaluated using the Franz diffusion cell and pig skin model.
[0052] (1) Cumulative Transmission Curve The cumulative permeation of free recombinant type III collagen and the functional composition prepared in Example 1 were measured at 0, 2, 4, 6, 8, 12, and 24 hours, respectively. Figure 9 As shown, the cumulative permeation of the functional composition experimental group (approximately 68.4 μg / cm³ over 24 hours) was [data missing]. 2 The levels were significantly higher than those in the free recombinant type III collagen experimental group (approximately 10.2 μg / cm³). 2 This indicates that the supramolecular assembly system (functional composition) provided by the present invention significantly promotes the transdermal penetration of collagen.
[0053] (2) Skin layer retention After a 24-hour transdermal assay, the amount of collagen retained in the stratum corneum, epidermis, and dermis was measured. Figure 10 As shown, the retention amount of the functional composition experimental group in all layers was significantly higher than that of the free recombinant type III collagen experimental group, especially in the dermis where the retention amount of the functional composition experimental group reached 30.4 μg / cm³. 2 The free recombinant type III collagen experimental group had only 1.1 μg / cm³. 2 This indicates that the supramolecular assembly system (functional composition) provided by the present invention can achieve deep delivery and retention of collagen.
[0054] (3) Observation by laser confocal microscope Fluorescently labeled collagen was used to trace the distribution of free recombinant type III collagen and the functional composition prepared in Example 1 in pig skin sections. Figure 11-12 As shown, the fluorescence signal of the free recombinant type III collagen experimental group was weak and mainly concentrated on the skin surface, while the fluorescence signal of the functional composition experimental group was strong and distributed deep into the dermis, which directly demonstrates the transdermal advantage of the supramolecular system of this invention.
[0055] (4) Transdermal absorption rate The 24-hour transdermal absorption rate (cumulative permeate volume / total administered dose × 100%) was calculated for both free recombinant type III collagen and the functional composition prepared in Example 1. Figure 13 As shown, the transdermal absorption rate of free recombinant type III collagen was only 8.2%, while the transdermal absorption rate of the functional composition experimental group was as high as 62.5%. This indicates that the supramolecular assembly system (functional composition) provided by the present invention has a synergistic effect on transdermal absorption.
[0056] 3. DPPH free radical scavenging ability To evaluate the antioxidant activity of the system, the free radical scavenging rate of different samples was determined using the DPPH method. The groups included the blank carrier experimental group, the free recombinant type III collagen experimental group, the free isorhamnetin experimental group, the free matrine experimental group, the physical mixture experimental group prepared in Comparative Example 1, and the functional composition experimental group prepared in Example 1.
[0057] like Figure 14 As shown, the scavenging rate of the functional composition experimental group was as high as 89.7%, significantly higher than that of other experimental groups (among which, the scavenging rate of the physical mixture experimental group was 52.3%). This indicates that the supramolecular assembly system (functional composition) provided by the present invention not only did not weaken the antioxidant activity, but also achieved a synergistic effect of isorhamnetin and matrine.
[0058] 4. Structural characterization (1) Fourier transform infrared spectroscopy (FTIR) FTIR spectra were performed on the free lichen polysaccharide experimental group, the free recombinant type III collagen experimental group, the free isorhamnetin experimental group, the free matrine experimental group, the physical mixture experimental group prepared in Comparative Example 1, and the functional composition experimental group prepared in Example 1.
[0059] like Figure 15 As shown, the characteristic peaks of the functional composition experimental group provided by the present invention show a significant shift compared to the characteristic peaks of each experimental group (e.g., the amide I band shifts from 1655 cm⁻¹). -1 Moved to 1640cm -1(or broadening). This indicates that non-covalent interactions such as hydrogen bonds formed between the components, proving the formation of supramolecular self-assembled structures.
[0060] (2) X-ray diffraction (XRD) The functional composition prepared in Example 1 was subjected to XRD analysis. Figure 16 As shown, the functional composition provided by this invention exhibits a typical broad diffuse peak (2θ about 22°) and no sharp crystal diffraction peaks, proving that the functional composition is an amorphous colloidal structure, consistent with the characteristics of supramolecular assemblies.
[0061] 5. Particle size and zeta potential (1) Dynamic light scattering (DLS) particle size distribution The functional composition prepared in Example 1 was subjected to dynamic light scattering (DLS) particle size distribution determination. For example... Figure 17 As shown, the functional composition provided by the present invention has an average particle size of about 120 nm and a narrow distribution (PDI < 0.2), indicating that a uniform nanoscale assembly is formed.
[0062] (2) Zeta potential Zeta potentials were measured in the blank carrier experimental group, the free recombinant type III collagen experimental group, and the functional composition experimental group prepared in Example 1. Figure 18 As shown, the Zeta potential of the free recombinant type III collagen experimental group was approximately -12.3 mV, the Zeta potential of the blank carrier experimental group was approximately -8.5 mV, and the Zeta potential of the functional composition experimental group was significantly reduced to -35.6 mV. This indicates that the functional composition provided by the present invention has an increased surface charge density, which is beneficial to the long-term stability of the system.
[0063] 6. Determination of the retention rate of isorhamnetin active ingredient (1) Light stability The free isorhamnetin experimental group, the conventional liposome-encapsulated isorhamnetin experimental group prepared in Comparative Example 2, and the functional composition experimental group prepared in Example 1 were placed under light for 0-10 days, and the retention rate of isorhamnetin active ingredient was measured.
[0064] like Figure 19 As shown, after 10 days of light exposure, the retention rate of isorhamnetin active ingredient in the free isorhamnetin experimental group was only 4%, while the retention rate of isorhamnetin active ingredient encapsulated by traditional liposomes was 32%, and the retention rate of isorhamnetin active ingredient in the functional composition experimental group was 85%. This demonstrates that the functional composition provided by this invention has excellent photoprotective effects on isorhamnetin.
[0065] (2) High temperature stability The free isorhamnetin experimental group, the conventional liposome-encapsulated isorhamnetin experimental group prepared in Comparative Example 2, and the functional composition experimental group prepared in Example 1 were respectively treated at 50°C for 24 hours, and the retention rate of isorhamnetin active ingredient was measured.
[0066] like Figure 20 As shown, after treatment at 50℃ for 24 hours, the retention rate of isorhamnetin active ingredient in the free isorhamnetin experimental group was only 12.5%, while the retention rate of isorhamnetin active ingredient in the traditional liposome-encapsulated isorhamnetin was 45.8%, and the retention rate of isorhamnetin active ingredient in the functional composition experimental group was 92.3%. This demonstrates that the functional composition provided by this invention can effectively resist thermal degradation.
[0067] (3) Long-term storage stability The free isorhamnetin experimental group and the functional composition experimental group prepared in Example 1 were stored at 25°C for 0, 30, 60 and 90 days, respectively, and the retention rate of isorhamnetin active ingredient was determined.
[0068] like Figure 21 As shown, after 90 days of storage at 25°C, the retention rate of isorhamnetin active ingredient in the free isorhamnetin experimental group was only 6%, while the retention rate of isorhamnetin active ingredient in the functional composition experimental group was 87%. This demonstrates that the functional composition provided by this invention can achieve long-term stability of isorhamnetin.
[0069] 7. Skin barrier repair effect (dynamic changes in TEWL value and skin hydration measurement) A skin barrier damage model was established (tape peeling method) to evaluate the repair capacity of different treatment groups. The preparation steps were as follows: Healthy male guinea pigs or Kunming mice (7-8 weeks old, weighing 180-220 g, purchased from Liaoning Changsheng Laboratory Animal Technology Co., Ltd.) were selected for SPF grade testing. Hair was removed from the back of the guinea pigs. Medical tape (3M, Micropore) was repeatedly applied and peeled off, with each application lasting 10 seconds, for 15-20 consecutive applications, until the transepidermal water loss (TEWL) value increased to more than three times the baseline value (>30 g / h / m²). 2 This indicates that the skin barrier damage model has been successfully established; Experimental groups: Blank control group: normal skin, no modeling, no test substance administered; Model group: After the skin barrier damage model was established, an equal amount of deionized water was applied; Positive control group: After the skin barrier damage model was established, 1% panthenol aqueous solution was applied. Free collagen group: After the skin barrier damage model was established, 0.8% free recombinant type III collagen solution was applied; Functional composition experimental group: After the skin barrier damage model was established, the functional composition prepared in Example 1 was applied.
[0070] The transepidermal water loss (TEWL) values of the blank control group, model group, positive control group, free collagen group, and functional composition experimental group were measured at 0, 1, 3, 5, and 7 days, respectively.
[0071] like Figure 22 As shown, the TEWL value of the model group continued to rise to 38 g / h / m 2 The TEWL value in the functional composition experimental group decreased to 12.8 g / h / m on day 7. 2 The functional composition experimental group showed similar results to the blank control group, but significantly outperformed the free collagen group. This demonstrates that the functional composition provided by this invention can rapidly repair damaged skin barriers.
[0072] The TEWL value comparison results on day 7 are as follows: Figure 23 As shown, the TEWL value of the functional composition experimental group on day 7 was 12.8 g / h / m 2 ) and the positive control group (13.5g / h / m 2 The levels were comparable to, and significantly lower than, those in the free collagen group (18 g / h / m). 2 This further verifies that the functional composition provided by the present invention has a synergistic and restorative effect.
[0073] The skin hydration levels of each treatment group on day 7 are as follows: Figure 24 As shown, the functional composition experimental group had the highest hydration level (58 a.u.), which was significantly better than the free collagen group (42 a.u.) and the model group (28 a.u.); it can be seen that the functional composition provided by the present invention can effectively improve the skin's moisturizing ability and assist in barrier repair.
[0074] 8. In vitro release behavior of isorhamnetin The cumulative release rate (0-24h) of isorhamnetin in the free isorhamnetin experimental group, the conventional liposome-encapsulated isorhamnetin experimental group prepared in Comparative Example 2, and the functional composition experimental group prepared in Example 1 was determined by the dialysis bag method.
[0075] like Figure 25 As shown, the free isorhamnetin experimental group released over 95% within 1 hour (burst release); the conventional liposome-encapsulated isorhamnetin experimental group prepared in Comparative Example 2 exhibited sustained-release characteristics, releasing 95% within 24 hours; the functional composition experimental group prepared in Example 1 released more gradually, releasing approximately 86% within 24 hours, and exhibited no burst release phenomenon. Therefore, the functional composition provided by this invention has good controlled-release performance, which is beneficial for prolonging the duration of drug efficacy.
[0076] 9. Antibacterial activity of matrine against Propionibacterium acnes The minimum inhibitory concentration (MIC) of Propionibacterium acnes was determined using the micro-broth dilution method in the blank carrier experimental group, the free matrine experimental group, the traditional liposome-encapsulated matrine experimental group prepared in Comparative Example 3, and the functional composition experimental group prepared in Example 1.
[0077] like Figure 26 As shown, the MIC of the free matrine experimental group was 128 μg / mL, the MIC of the traditional liposome-encapsulated matrine experimental group was 64 μg / mL, the blank carrier experimental group had no antibacterial activity (MIC>512 μg / mL), and the MIC of the functional composition experimental group prepared in Example 1 was as low as 8 μg / mL. This indicates that the functional composition provided by the present invention greatly enhances the antibacterial efficacy of matrine, which may be related to the improved dispersibility and cell membrane permeability of matrine by the assembly.
[0078] 10. Safety Evaluation (1) Cytotoxicity (MTT assay) HaCaT cells were treated with different concentrations (0, 0.1, 0.5, 1, 2, 5 mg / mL) of blank carrier and the functional composition prepared in Example 1 for 24 h, and the survival rate of HaCaT cells was measured.
[0079] like Figure 27 As shown, the blank carrier and the functional composition had no significant effect on cell viability at any concentration (both were above 85%), and the functional composition still achieved a viability of 94% at a high concentration (5 mg / mL). This indicates that the functional composition provided by the present invention has good cell compatibility.
[0080] (2) Chicken embryo allantoic membrane stimulation test The blank carrier and the functional composition prepared in Example 1 were used to treat the chicken embryo allantoic membrane, and the stimulation scores were recorded. The scoring criteria were as follows: the vascular reaction of the chicken embryo allantoic membrane was observed within 5 minutes of treatment, and the occurrence time and degree of bleeding, vascular dissolution and coagulation were recorded. Each item was scored from 0 to 3 points. The total stimulation score = (bleeding score + vascular dissolution score + coagulation score) / 3. A score < 1 was considered non-irritating.
[0081] like Figure 28 As shown, the score of the blank carrier experimental group was 0.8, and the score of the functional composition experimental group was 0.2, both meeting the non-irritating standard (<1 point). Furthermore, the score of the functional composition experimental group was lower than that of the blank carrier experimental group. This indicates that the functional composition provided by the present invention has lower irritation.
[0082] (3) Red blood cell hemolysis test The blank carrier and the functional composition prepared in Example 1 were co-incubated with 2% red blood cell suspension, and the hemolysis rate was measured.
[0083] like Figure 29 As shown, the hemolysis rate in the blank carrier experimental group was 3.2%, and the hemolysis rate in the functional composition experimental group was only 0.8%, both below the safety limit of 5%. Therefore, the functional composition provided by this invention has no significant risk of hemolysis.
[0084] The above safety data indicate that the self-assembled system of the present invention is safe and reliable within the effective concentration range, and has lower irritation than the blank carrier.
[0085] 11. Verification of in vivo repair effects (collagen and hydroxyproline content) Using an animal model of skin injury (UV irradiation or mechanical injury), skin tissue was collected after drug administration, and the collagen and hydroxyproline content was determined according to the kit method.
[0086] Steps for preparing animal models of skin lesions (ultraviolet irradiation method): SPF-grade healthy male Balb / c nude mice (7-8 weeks old, weighing 180-220 g, purchased from Liaoning Changsheng Experimental Animal Technology Co., Ltd.) were selected, and the skin on their backs was dehaired. UVB ultraviolet light (wavelength 311 nm, irradiance 120 mJ / cm²) was used for irradiation. 2 Irradiate once a day for 10 minutes each time, for 7 consecutive days, until obvious erythema, roughness and thickening of the skin appear, which is considered to be a successful establishment of the photoaging skin damage model.
[0087] Administration procedure: After successful modeling, the test substance was applied once a day, with an application area of 2 cm × 2 cm and an application volume of 100 μL per animal. The administration was continued for 14 consecutive days. 24 hours after the last administration, the animals were sacrificed, and the skin tissue from the back was taken, cut into pieces, and the collagen and hydroxyproline content was determined according to the instructions of the kit (purchased from Nanjing Jiancheng Biotechnology Institute).
[0088] Experimental Groups: Normal control group: Normal skin that has not been exposed to ultraviolet light and has not been given any test substance; Model group: After successful modeling by ultraviolet irradiation, apply an equal amount of deionized water; Positive control group: After successful modeling by ultraviolet irradiation, commercially available vitamin C ethyl ether serum (concentration of 2%) was applied. Free collagen group: After successful modeling by UV irradiation, a 0.8% free recombinant type III collagen solution was applied. Functional composition experimental group: After successful modeling by ultraviolet irradiation, the functional composition prepared in Example 1 was applied.
[0089] (1) Determination of collagen content The collagen content of the blank control group, model group, positive control group, free collagen group and functional composition experimental group was determined.
[0090] like Figure 30 As shown, the collagen content in the normal control group was 85 μg / mg, the collagen content in the model group decreased to 32 μg / mg, the collagen content in the positive control group rebounded to 78 μg / mg, the collagen content in the free collagen group was 65 μg / mg, and the collagen content in the functional composition experimental group was as high as 92 μg / mg, even exceeding that of the normal control group. This indicates that the functional composition provided by the present invention can significantly promote the synthesis and regeneration of collagen in damaged skin.
[0091] (2) Determination of hydroxyproline content The hydroxyproline content was determined in the blank control group, model group, positive control group, free collagen group, and functional composition experimental group. Hydroxyproline is a characteristic amino acid of collagen, and its content directly reflects the collagen level.
[0092] like Figure 31 As shown, the hydroxyproline content in the model group was only 15 μg / mg, while the hydroxyproline content in the functional composition experimental group was 45 μg / mg, which was significantly higher than that in the free collagen group (30 μg / mg) and the positive control group (38 μg / mg), further confirming that the functional composition provided by the present invention has a strong collagen repair ability.
[0093] In summary, this invention addresses five core technical pain points of recombinant type III collagen in cosmetic applications: poor stability, low transdermal penetration and retention efficiency, insufficient synergy among multiple components, difficulty in balancing high efficacy and high tolerability, and high industrial production costs. It innovatively constructs a three-dimensional supramolecular self-assembly system with the electrostatic interaction between lichen polysaccharide and recombinant type III collagen as a rigid framework. This system is formed through the synergistic effects of multiple non-covalent bonds, including hydrogen bonds, hydrophobic host-guest inclusion, and π-π stacking. The invention clarifies the specific ratio range of the four core components—lichen polysaccharide, recombinant type III collagen, isorhamnetin, and matrine—as well as the stepwise dropwise addition and gradient self-assembly preparation process. The four components and the specific preparation process complement each other and are indispensable, jointly achieving stable encapsulation, efficient delivery, and synergistic effects of the active ingredients.
[0094] This invention overcomes the core bottlenecks of existing technologies at the molecular level through a supramolecular self-assembly structure: First, the constructed three-dimensional network forms multiple physical barriers and chemical protections for recombinant type III collagen, isorhamnetin, and matrine, significantly improving the structural integrity and bioactivity retention of active ingredients over a wide temperature range, wide pH range, and long-term storage, solving the industry problem of easy degradation of collagen and easy inactivation of active ingredients; Second, the nanoscale uniform assembly significantly improves the transdermal penetration efficiency and deep skin retention capacity of active ingredients, while achieving long-term sustained release of active ingredients, greatly improving bioavailability and solving the problem of large collagen molecules being difficult to penetrate the skin and easily lost; Third, the four components, through separation... The intermolecular interactions form a functionally integrated network, achieving synergistic effects of skin repair, anti-oxidation, anti-inflammatory and antibacterial properties, and moisturizing film formation, breaking through the limitations of simple physical mixing where "1+1<2" is the only result. Fourth, through the inclusion and immobilization of the supramolecular network, the irritation of active ingredients directly contacting the skin is reduced, maintaining excellent skin tolerance even at high active concentrations, making it suitable for various skin types such as sensitive skin, and achieving a balance between high efficacy and high safety. Fifth, the entire preparation process is completed in a mild aqueous phase, without the need for organic solvents, high-end freeze-drying equipment, or complex synthetic reactions. The process is simple, with good batch stability, significantly reducing industrial production costs and possessing strong industrialization potential.
[0095] The functional composition provided by this invention, after systematic structural characterization, in vitro physicochemical experiments, cell experiments, animal experiments and human trials, has demonstrated excellent storage stability, skin barrier repair and anti-aging effects, good biosafety and skin feel. It provides a brand-new technical approach and solution for the research and development of recombinant collagen-based functional cosmetics, and has broad market application prospects and industrialization value in the fields of anti-aging and sensitive skin repair cosmetics.
[0096] The specific embodiments of the present invention disclosed above are merely illustrative of the invention. These embodiments do not exhaustively describe all details, nor do they limit the invention to the specific embodiments described. Many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention.
Claims
1. A functional composition based on molecular self-assembly, characterized in that, The functional composition, by weight percentage, comprises the following components: 0.1%-8.0% lichen polysaccharide, 0.05%-5.0% recombinant type III collagen, 0.005%-1.0% isorhamnetin, and 0.01%-2.0% matrine; the preparation steps of the functional composition are as follows: S1: Add lichen polysaccharide to deionized water while stirring, and continue stirring at 40-60℃ until completely dissolved to form a homogeneous and transparent colloidal solution. Cool to room temperature to obtain phase A. S2: Add recombinant type III collagen to deionized water and stir or swell until completely dissolved at room temperature to obtain phase B; S3: Under low-speed stirring conditions, phase B obtained in S2 is added dropwise to phase A obtained in S1. After the addition is complete, stirring is continued for 30-90 minutes to form a primary gel network through self-assembly. S4: Dissolve isorhamnetin and matrine together in a polyol, and heat to aid dissolution to obtain phase C; S5: Under low-speed stirring conditions, phase C obtained in S4 is added dropwise to the primary gel network obtained in S3. After the addition is complete, the resulting mixture is transferred to a homogenizer for homogenization, allowed to stand and mature, and the pH value is adjusted to 5.5-6.
5. The functional composition is obtained by vacuum degassing and filtration. The low-speed stirring conditions described in S3 and S5 are 200-400 rpm; The homogenization conditions were: 12,000 rpm and 8 minutes.
2. The functional composition according to claim 1, characterized in that, The room temperature mentioned in S1 and S2 is 20-25℃.
3. The functional composition according to claim 1, characterized in that, The polyols mentioned in S4 include propylene glycol, butanediol, or glycerol; the heating conditions for solubilization are: temperature ≤ 50℃.
4. The functional composition according to claim 1, characterized in that, The conditions for static curing described in S5 are: temperature of 35-45℃ and time of 1-3 hours.
5. A self-assembled skincare product made from recombinant type III collagen, characterized in that, The self-assembly skincare product contains the functional composition according to any one of claims 1 to 4, as well as a cosmetically acceptable carrier and excipients.
6. The use of the functional composition according to any one of claims 1 to 4 in the preparation of anti-aging and skin barrier repair cosmetics.
Citation Information
Patent Citations
Type III recombinant humanized collagen transdermal delivery composition and preparation method thereof
CN120713791A
Chitosan-collagen synergistic self-assembly fiber material and preparation method thereof
CN120842622A